ALOKASI DAN DISTRIBUSI AIR DI DAERAH IRIGASI JATILUHUR INDONESIA: EVALUASI DAN TANTANGAN - Sudiana, Rahmat; Yudianto, Doddi; Xiuju, Zhang (JURNAL SPEKTRAN; Vol 5 No 2 (2017): Vol. 5, No. 2, Juli 2017, 2017)
Indonesia has rich natural resources including water resources. The abundance of water resources is characterized by an annual rainfall averaging about 2790 mm. Jatiluhur irrigation area is one of large irrigation system in Indonesia which plays main role for national food and agriculture defense. It receives water from Djuanda Multipurpose Reservoir located in Citarum River West Java Indonesia. This reservoir is responsible to irrigate 240,000 ha paddy field, raw water for domestic municipal industrial (DMI) and hydropower generation. The water is released from the reservoir to Curug Diversion Weir where the water is diverted to West Tarum Canal (WTC), East Tarum Canal (ETC) and North Tarum Canal (NTC). Mechanisms for water allocation and distribution are professionally managed by Jasa Tirta II Public Corporation (PJT II). Although provision of irrigation system seems performing well, some aspects still need improvement and development. The important issue for improvement is quality and reliability of basic data required to prepare the water allocation plan and distribution schedule. Taking into account future developments which will increase combined water demand. Consequently, there is a need to investigate how efficient the system is working currently and which improvements can be proposed to increase overall water use efficiency. Water balance in the Jatiluhur irrigation system theoretically capable to fulfill water demand until 2025 but climate change issue should be considered as period of dry season and wet season will be shifted. Based on the research scenario, dry season will be longer and wet season will be shorter with more intense rainfall.     Keywords: Jatiluhur irrigation area, Djuanda multipurpose reservoir, water allocation & distribution, water efficiency, water balance